2017 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--28145
|View full text |Cite
|
Sign up to set email alerts
|

Developing Leadership through an Immersive Service-Oriented International Internship

Abstract: with extensive experience in sustainable development, construction, and project management in Haiti. He has spent almost a year in Haiti's rural Central Plateau on projects ranging from repairing small schools, water distribution/treatment systems, sanitation infrastructure, and aquaculture programs. Additionally, he is the founding director of Clemson's chapter of Grand Challenge Scholars.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…One participant quoted in Smith and Lucena's (2016) study identifies the importance of designing in context: "[A]s an engineer I would design not only for the job but for how the job affects the [user]…If I am designing a piece of frack blender, I would put myself in the mechanics shoes" (p. 17). Gordon et al (2017) reported on students' ability to make a difference from their engineering work. They note that students who participated in an international service-oriented internship identify that the extent to which their ability to change the world and local community was greater than the selfidentified ability of those students who did not complete an internship.…”
Section: Designing Within a Larger Social Contextmentioning
confidence: 99%
“…One participant quoted in Smith and Lucena's (2016) study identifies the importance of designing in context: "[A]s an engineer I would design not only for the job but for how the job affects the [user]…If I am designing a piece of frack blender, I would put myself in the mechanics shoes" (p. 17). Gordon et al (2017) reported on students' ability to make a difference from their engineering work. They note that students who participated in an international service-oriented internship identify that the extent to which their ability to change the world and local community was greater than the selfidentified ability of those students who did not complete an internship.…”
Section: Designing Within a Larger Social Contextmentioning
confidence: 99%
“…The class focuses on progressively strengthening the students' skills each semester. Students, faculty, and nonprofit and industry partners have previously anecdotally noted that the unique structure cultivates skills and mindsets that are in demand by industry but are often underdeveloped in new graduates 3 .…”
Section: Introductionmentioning
confidence: 99%